Combinatorial interpretation of raney numbers and tree enumerations - Pah, Chin Hee; Wahiddin, Mohamed Ridza (Scientific Research Publishing, 2015)
A new combinatorial interpretation of Raney numbers is proposed. We apply this combinatorial interpretation to solve several tree enumeration counting problems. Further a generalized Catalan triangle is introduced and some of its properties are proved.